PHYSICOCHEMICAL CHARACTERIZATION OF FLOURS CASSAVA FROM THE IRURAMA COMMUNITY, SANTARÉM-PA, BRAZIL - Antonio Correa Matos do Amaral, Marcos; Azevedo da Silva, Obed; Rangel Rodrigues, Rogério; Lita Padinha Correa Romano, Maria; Maria Tribuzy de Magalhães Cordeiro, Angela; de Oliveira Costa, Jéfferson (REVISTA DE AGRICULTURA, 2025)
This study investigated the quality standards of cassava flours produced in the Irurama community in the municipality of Santarém, Pará, Brazil. In order to adapt the product to current legislation, cassava flours from five varieties of the mixed group (BRS Kiriris, BRS Poti, BRS Mari, Jurará and Manivão) were analyzed for chemical and physical characteristics. Granulometric determinations of the cassava flours and physical-chemical analyses were performed to characterize the moisture, lipid, protein, carbohydrate and ash content. Water activity, total acidity, pH and total sugars were also evaluated. In the granulometric analysis of cassava flours, it was observed that the varieties had different retentions in sieves of 8, 12, 16, 30, 40, 50 and 70 mesh. Regarding the chemical composition, a positive relationship was observed between the granulometry of cassava flours and moisture. Higher moisture contents were found in the varieties BRS Mari and BRS Kiriris. The cassava flours produced from the Manivão and BRS Kiriris varieties presented higher pH values. All cassava flours of the studied varieties presented moisture contents lower than 13%, which is the maximum value allowed by Brazilian legislation. In general, all flour samples of the five cassava varieties analyzed presented results consistent with Brazilian legislation.